The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.2172/1057367
|View full text |Cite
|
Sign up to set email alerts
|

FY12 ARRA-NRAP Report ? Studies to Support Risk Assessment of Geologic Carbon Sequestration

Abstract: SummaryThis report summarizes results of research conducted during FY 2012 to support the assessment of environmental risks associated with geologic carbon dioxide (CO 2 ) sequestration and storage. Several research focus areas are ongoing as part of this project. This includes the quantification of the leachability of metals and organic compounds from representative CO 2 storage reservoir and caprock materials, the fate of metals and organic compounds after release, and the development of a method to measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…In the subsurface, the injected scCO 2 produces regions in which the full spectrum of mutual CO 2 -H 2 O solubility can occur [6][7][8][9]. In basalt reservoirs, the CO 2 -rich (water-bearing scCO 2 ) fluids are highly reactive with regard to the minerals present [10], and the scCO 2 may mobilize the organics, as scCO 2 is an effective solvent of organic matter [11], which has been observed in the field and in experiments with geomaterials [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. In our recent investigation, we demonstrated that simple, naturally abundant organic ligands (the protonated forms of acetate, malonate, oxalate, and citrate) were transported through water-saturated scCO 2 and their presence impacted the carbonation of forsterite [25].…”
Section: Introductionmentioning
confidence: 99%
“…In the subsurface, the injected scCO 2 produces regions in which the full spectrum of mutual CO 2 -H 2 O solubility can occur [6][7][8][9]. In basalt reservoirs, the CO 2 -rich (water-bearing scCO 2 ) fluids are highly reactive with regard to the minerals present [10], and the scCO 2 may mobilize the organics, as scCO 2 is an effective solvent of organic matter [11], which has been observed in the field and in experiments with geomaterials [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. In our recent investigation, we demonstrated that simple, naturally abundant organic ligands (the protonated forms of acetate, malonate, oxalate, and citrate) were transported through water-saturated scCO 2 and their presence impacted the carbonation of forsterite [25].…”
Section: Introductionmentioning
confidence: 99%